Single molecule sequencing reveals response of manganese-oxidizing microbiome to different biofilter media in drinking water systems. (15th March 2020) - Zhao, Xin; Liu, Bingfeng; Wang, Xiuheng; Chen, Chuan; Ren, Nanqi; Xing, Defeng
Abstract: Rapid sand biofiltration (RSBF) is widely used for the removal of contaminants from drinking water treatment systems. Biofilm microbiomes in the biofilter media play essential roles in biotransformation of contaminants, but is not comprehensively understood. This study reports on Mn(II) oxidation and the core microbiomes in magnetite sand RSBF (MagS–RSBF) and manganese sand RSBF (MnS–RSBF). MnS–RSBF showed a relatively higher Mn(II) removal rate (40–91.2%) than MagS–RSBF during the start-up. MagS–RSBF and MnS–RSBF had similar Mn(II) removal rates (94.13% and 99.16%) over stable operation for 80 days. Mn(II) removal rates at different depths in the MnS–RSBF reactor significantly changed with operation time, and the filter in the upper layer of MnS–RSBF made the largest contribution to Mn(II) oxidation once operation had stabilized. PacBio single molecule sequencing of full-length 16S rRNA gene indicated that biofilter medium had a significant impact on the core microbiomes of the biofilms from the two biofilters. The magnetite sand biofilter facilitated the enrichment of Mn(II)-oxidizing biofilms. The dominant populations consisted of Pedomicrobium, Pseudomonas, and Hyphomicrobium in the RSBF, which have been affiliated with putative manganese-oxidizing bacteria (MnOB). The relative abundance of Pedomicrobium manganicum increased with operation time in both RSBF reactors. In addition, Nordella oligomobilis and Derxia gummosa were statistically correlated with Mn(II) oxidation. Species-species co-occurrence networks indicated that the microbiome of MnS–RSBF had more complex correlations than that of MagS–RSBF, implying that biofilter medium substantially shaped the microbial community in the RSBF. Hyphomicrobium and nitrite-oxidizing Nitrospira moscoviensis were positively correlated. The core microbiomes' composition of both RSBF reactors converged over operation time. A hybrid biofilter medium with magnetite sand and manganese sand may therefore be best in rapid sand filtration for Mn(II) oxidation. Graphical abstract: Image 1 Highlights: Biofilter medium influenced Mn(II) oxidation and biofilm microbiome in RSBF. Mn(II) oxidation and microbiomes changed in time and space in the biofilters. Mn(II) oxidation in the upper layers of MnS–RSBF increased over time. Magnetite sand-RSBF had better initial enrichment of Mn-oxidizing bacteria. Manganese sand-RSBF had a more complex species-species co-occurrence network.